Eccentric compression of large varicose veins after foam sclerotherapy using a novel silicone gel pad - Ragg, J. C. (Phlebologie, 2014)
Ziel: Wir evaluierten eine neuartige exzentrische Kompression, die ultraschalltransparentes Silikon-Gel zwischen selbstklebenden Fo-lien als individuelles Druckpolster verwendet.Methodik: Es wurden 120 Patienten mit 148 oberflächlichen Varizen (Ø 5,1–13,7 mm; MW: 7,6) nach Schaumverödung einbezogen: A) segmental randomisiert mit fokaler Kompression durch Silikon-Gel-Polster (Venartis® SGP) für 14 Tage plus Kompressionsstrumpf KKl. 2 (KS) tagsüber für 28 Tage, oder B) nur KS. Das SGP-System besteht aus einer selbstklebenden Basisfolie, auf die Silikon dem Venenverlauf folgend aufgetragen wird. Eine zweite Folie bedeckt Gel und Basisfolie. Den Patienten war Duschen erlaubt. Ermittelt wurden Querschnittsreduktion (QR, Ultra-schallscans) sowie klinische Parameter nach 2, 4 und 8 Wochen.Ergebnisse: Segmente mit SGP zeigten gegenüber KS eine höhere QR, im Mittel 52,5 vs. 23,1 % (2 Wo), 48,4 vs. 28,9 % (4 Wo) und 66,7 vs. 39,2 % (8 Wo). Entzündungsreaktionen waren unter SGP mit 12,4 vs. 39,9 % signifikant seltener, ebenso Verfärbungen mit 10,8 vs. 35,1 %. Minithrombektomien (8,1 vs. 29,7 %) und orale Analgetika (6,8 vs. 19,6 %) wurden seltener benötigt. Unerwünschte Wirkungen: Diskrete Hautirritationen (10,1 %).Schlussfolgerung: Indikationsspezifische Silikonhärten, Dosierungen, Tragezeiten und die Höhe externer Drücke bedürfen weiterer Untersuchungen, wobei die Ultraschalltransparenz neue Wege eröffnet.Aim: After sclerotherapy of varicosities, eccentric compression is meant to provide rapid and symptom-free vein regression. We evaluated a new compression modality consisting of thin adhesive films and ultrasound transparent silicone gels, individually applied along treated veins.Methods: 120 patients were included with 148 superficial varicosities of 5.1–13.7 mm in diameter (mean: 7.6) undergoing foam sclerotherapy (Aethoxysklerol 1 %, filtrated room air; ratio: 1+4). Postinterventional treatment was randomized to A) silicone gel pad (SGP, Venartis® Inc.) on one half of the vein length for 2 weeks plus compression stocking (German class 2) for 4 weeks, or B) compression stocking alone. The SGP consists of a thin adhesive film sheet to serve as a mechanical skin protection, silicone gels with final hardness of Shore-A 5–22 applied on the film from cartridges along the vein following all curves, and a second adhesive film sheet to cover the silicone. Patients were allowed to take daily showers with SGP in place. Vein diameters were measured by ultrasound and clinical criteria determined after 2, 4 and 8 weeks.Results: Vein segments receiving focal compression with SGP showed a faster regression: 52.5 % (22.4–74.2 %) vs. 23.1 % (8.1–36.7 %) after 2 weeks, 48.4 % (33.2–64.5 %) vs. 28.9 % (26.1–43.1 %) after 4 weeks and 66.7 % (31.1–82.4 %) vs. 39.2 % (21.0–61.8 %) after 8 weeks. The frequency of inflammatory reactions was lower when using SGP (12.4 vs. 39.9 %). The frequency of mini-thrombectomies was lowered to 8.1 % with SGP, versus 29.7 % in non-SGP segments, and oral analgetics were given in just 6.8 % (vs. 19.6 %). Discolorations were observed at week 8 in 10.8 % of the cases, vs. 35.1 % when using concentric compression only. Unwanted side effects of SGP were marginal skin irritations (10.1 %), leading to a wearing time of 5–12 days in 2.0 % of the cases (3/148). There were no other adverse reactions, in particular no allergies.Conclusion: Venartis® SGP is a safe, effective and comfortable modality to support vein regression after sclerotherapy of varicosities. The indications for hard and soft silicones, the dosage in relation to vein diameter and position, wearing times and external pressure have to undergo further studies. As the device is ultra-sound transparent, examinations of treated veins will be possible with the pad in place to optimize the degree of vein compression.
Keywords: Kompression; Silikon-Gel; Gel-Polster; Schaumverödung; Analgetika